Architecture and structure of the kidneys of Gracilinanus microtarsus (Didelphimorphia: Didelphidae) (WAGNER, 1842) - Prado, César Vinícius Gil Braz do; Carniatto, Caio Henrique de Oliveira; Santos, Ana Carolina Martins dos; Rodrigues, Rosângela Felipe; Favaron, Phelipe Oliveira; Rodrigues, Márcio Nogueira; Miglino, Maria Angélica (Brazilian Journal of Veterinary Research and Animal Science, 2015)
Gracilinanus microtarsus is a South American marsupial that belongs to Didelphimorphia order and Didelphidae family. The gross and microscopic anatomy of the kidneys of G. microtarsus was studied. The species has a pair of kidneys located in the sublumbar region of the abdominal cavity, close to the spine. The right kidney is cranial to the left kidney, and both have a bean shape. In a longitudinal cut, the kidney has defined areas, such as the renal cortex and medulla, as well as the renal papilla, calices and renal pelvis. The kidney of Gracilinanus microtarsus is classified as unilobado with a smooth surface and showing microscopic aspect similar to the kidneys of dogs and cats.